Unveiling the Emerging Role of Xanthine Oxidase in Acute Pancreatitis: Beyond Reactive Oxygen Species - Chenxia Han; Yaling Wu; Juan Rong; Qing Xia; Dan Du (Antioxidants)
Acute pancreatitis (AP) is a potentially fatal acute digestive disease that is widespread globally. Although significant progress has been made in the previous decade, the study of mechanisms and therapeutic strategies is still far from being completed. Xanthine oxidase (XO) is an enzyme that catalyzes hypoxanthine and xanthine to produce urate and is accompanied by the generation of reactive oxygen species (ROS) in purine catabolism. Considerable preclinical and clinical studies have been conducted over many decades to investigate the role of XO in the pathogenesis of AP and its potential targeting therapeutic value. There is no doubt that the ROS generated by irreversibly activated XO participates in the local pancreas and multiple organ failure during AP. However, the optimal timing and doses for therapeutic interventions targeting XO in animal studies and the clinic, as well as the additional molecular mechanisms through which XO contributes to disease onset and progression, including metabolic regulation, remain to be elucidated. This review summarized the benefits and contradictions of using XO inhibitors in animal models, offered mechanisms other than ROS, and discussed the difficulties faced in clinical trials. We hope to provide a perspective on the future worthwhile basic and clinical research on XO by analyzing its chemical and biological characteristics, as well as the progress of its regulatory mechanisms in AP.